Attenuation of carotid neointimal formation after direct delivery of a recombinant adenovirus expressing glucagon-like peptide-1 in diabetic rats. Issue 2 (4th October 2016) - Lim, Soo; Lee, Gha Young; Park, Ho Seon; Lee, Dong-Hwa; Tae Jung, Oh; Kyoung Min, Kim; Kim, Young-Bum; Jun, Hee-Sook; Hak Chul, Jang; Park, Kyong Soo
Abstract : Aims: Enhancement of glucagon-like peptide-1 (GLP-1) reduces glucose levels and preserves pancreatic β-cell function, but its effect against restenosis is unknown. Methods and results: We investigated the effect of subcutaneous injection of exenatide or local delivery of a recombinant adenovirus expressing GLP-1 (rAd-GLP-1) into carotid artery, in reducing the occurrence of restenosis following balloon injury. As a control, we inserted β-galactosidase cDNA in the same vector (rAd-βGAL). Otsuka Long-Evans Tokushima rats were assigned to three groups ( n = 12 each): (1) normal saline plus rAd-βGAL delivery (NS + rAd-βGAL), (2) exenatide plus rAd-βGAL delivery (Exenatide + rAd-βGAL), and (3) normal saline plus rAd-GLP-1 delivery (NS + rAd-GLP-1). Normal saline or exenatide were administered subcutaneously from 1 week before to 2 weeks after carotid injury. After 3 weeks, the NS + rAd-βGAL group showed the highest intima–media ratio (IMR; 3.73 ± 0.90), the exenatide + rAd-βGAL treatment was the next highest (2.80 ± 0.51), and NS + rAd-GLP-1 treatment showed the lowest IMR (1.58 ± 0.48, P < 0.05 vs. others). The proliferation and migration of vascular smooth muscle cells and monocyte adhesion were decreased significantly after rAd-GLP-1 treatment, showing the same overall patterns as the IMR. In injured vessels, the apoptosis was greater and MMP2 expression was less in the NS + rAd-GLP-1 than in the exenatide or rAd-βGAL groups. In vitro expressions of matrix metalloproteinases-2 and monocyte chemoattractant protein-1 and nuclear factor-kappa-B-p65 translocation were decreased more in the NS + rAd-GLP-1 group than in the other two groups (all P < 0.05). Conclusion: Direct GLP-1 overexpression showed better protection against restenosis after balloon injury via suppression of vascular smooth muscle cell migration, increased apoptosis, and decreased inflammatory processes than systemic exenatide treatment. This has potential therapeutic implications for treating macrovascular complications in diabetes.